2008
DOI: 10.1002/chp.177
|View full text |Cite
|
Sign up to set email alerts
|

After the crash: Research-based theater for knowledge transfer

Abstract: Responses supported the effectiveness of drama as a knowledge translation strategy and identified its potential to impact practice positively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(76 citation statements)
references
References 31 publications
(29 reference statements)
1
74
0
1
Order By: Relevance
“…In all of these studies, theatre was identified as research-based theatre. That is, the authors explicitly created a play or a performance based on the findings of a prior research study they were involved in (Colantonio et al, 2008;Gray et al, 2000;Gray, Fitch, LaBrecque & Greenberg, 2003;Mitchell, Jonas-Simpson & Ivonoffski, 2006;Rosenbaum, Ferguson & Herwaldt, 2005). The studies in this review were only those that included arts-based methods; on that basis we did not include the primary study on which the research-based theater originated.…”
Section: Analytic Findingsmentioning
confidence: 97%
“…In all of these studies, theatre was identified as research-based theatre. That is, the authors explicitly created a play or a performance based on the findings of a prior research study they were involved in (Colantonio et al, 2008;Gray et al, 2000;Gray, Fitch, LaBrecque & Greenberg, 2003;Mitchell, Jonas-Simpson & Ivonoffski, 2006;Rosenbaum, Ferguson & Herwaldt, 2005). The studies in this review were only those that included arts-based methods; on that basis we did not include the primary study on which the research-based theater originated.…”
Section: Analytic Findingsmentioning
confidence: 97%
“…8 These approaches have been used to facilitate learning and to develop empathetic understanding. [9][10][11][12][13][14] Film can be a succinct, accessible and practical means of disseminating findings. 15,16 Existing reviews indicate a need for research to evaluate knowledge mobilised through artsbased research.…”
mentioning
confidence: 99%
“…Knowledge disseminated this way may effectively reach diverse groups of stakeholders, including but not limited to community members and policy makers, and address the full range of sensory literacy levels. It often enables a more empathic participation of the viewers, stimulates new forms of public dialogue and may advocate social changes (Colantonio et al, 2008;Gergen & Gergen, 2011).…”
Section: Discussionmentioning
confidence: 99%